(untitled) (Academicia Globe: Inderscience Research, 2021)
This article highlights some of the techniques and strategies of teaching the Russian language used by the teacher in the national audience. The application of advanced technologies and teaching methods, contributing to the formation and development of monologue Russian speech of students of national groups, their practical mastery of speech in a non-native language is proposed.